Association between conflicts of interest and favourable recommendations in clinical guidelines, advisory committee reports, opinion pieces, and narrative reviews: systematic review. (9th December 2020) - Nejstgaard, Camilla H; Bero, Lisa; Hróbjartsson, Asbjørn; Jørgensen, Anders W; Jørgensen, Karsten J; Le, Mary; Lundh, Andreas
Abstract: Objective: To investigate the association between conflicts of interest and favourable recommendations in clinical guidelines, advisory committee reports, opinion pieces, and narrative reviews. Design: Systematic review. Eligibility criteria: Studies that compared the association between conflicts of interest and favourable recommendations of drugs or devices (eg, recommending a drug) in clinical guidelines, advisory committee reports, opinion pieces (eg, editorials), or narrative reviews. Data sources: PubMed, Embase, Cochrane Methodology Register (from inception to February 2020), reference lists, Web of Science, and grey literature. Data extraction and analysis: Two authors independently extracted data and assessed the methodological quality of the studies. Pooled relative risks and 95% confidence intervals were estimated using random effects models (relative risk >1 indicates that documents with conflicts of interest more often had favourable recommendations than documents with no conflicts of interest). Financial and non-financial conflicts of interest were analysed separately, and the four types of documents were analysed separately (preplanned) and combined (post hoc). Results: 21 studies that analysed 106 clinical guidelines, 1809 advisory committee reports, 340 opinion pieces, and 497 narrative reviews were included. Unpublished data were received for 11 studies (eight full datasets and three summary datasets). 15 studies showed risk of confounding because the compared documents could differ in factors other than conflicts of interest (eg, different drugs used for different populations). The relative risk for associations between financial conflicts of interest and favourable recommendations for clinical guidelines was 1.26 (95% confidence interval 0.93 to 1.69; four studies of 86 clinical guidelines), for advisory committee reports was 1.20 (0.99 to 1.45; four studies of 629 advisory committee reports), for opinion pieces was 2.62 (0.91 to 7.55; four studies of 284 opinion pieces), and for narrative reviews was 1.20 (0.97 to 1.49; four studies of 457 narrative reviews). An analysis of all four types of documents combined supported these findings (1.26, 1.09 to 1.44). In one study that investigated specialty interests, the association between including radiologists as authors of guidelines and recommending routine breast cancer was: relative risk 2.10, 95% confidence interval 0.92 to 4.77; 12 clinical guidelines). Conclusions: We interpret our findings to indicate that financial conflicts of interest are associated with favourable recommendations of drugs and devices in clinical guidelines, advisory committee reports, opinion pieces, and narrative reviews. Limitations of this review were risk of confounding in the included studies and the statistical imprecision of individual analyses of each document type. It is not certain whether non-financial conflicts of interest influence recommendations. Systematic review registration: Cochrane Methodology Review Protocol MR000040.